Effects of change in muscle temperature on pre and post vascular responses - Nailwal, Brijesh (2025)
ABSTRACT Introduction. Muscle temperature plays a critical role in exercise performance and recovery, particularly in vascular responses such as reactive hyperemia. While temperature is known to influence vascular tone and oxygen availability, its effect on RH following high-intensity exercise remains unclear. Understanding how muscle temperature impacts post-exercise vascular responses can provide insights into optimizing recovery strategies for athletes and individuals with vascular impairments. Therefore, this study aimed to investigate how muscle temperature modulation influences RH responses pre- and post-3-minute all-out cycling test (3MT). Methods. Seven healthy participants (5 males, and 2 females; age: 26 ± 3.83 years) completed three randomized conditions: hot, cold, and thermoneutral. Muscle temperature was modulated (±3 ℃) using water immersion and perfusion cuffs, followed by RH assessment pre- and post-exercise via near-infrared spectroscopy (NIRS). The RH response was assessed through max tissue saturation index (Max TSI), time to peak, reperfusion slope, area under curve (AUC), and change in TSI in the first 10 seconds (Δ 10 TSI). Non-parametric (Friedman) tests were performed to compare pre- and post-exercise conditions. Results. Pre-exercise, muscle temperature was significantly different between conditions (Neutral: 34.45 ± 0.82°C, Hot: 37.27 ± 0.72°C, Cold: 30.22 ± 0.91°C; p < 0.005), but this did not significantly affect RH responses across conditions. Post-exercise, muscle temperature remained significantly different (Neutral: 35.59 ± 0.63°C, Hot: 37.39 ± 0.38°C, Cold: 33.84 ± 1.63°C; p < 0.005). Post-exercise, Max TSI was significantly higher in the hot condition (82.03 ± 3.51%) compared to the cold condition (79.94 ± 3.29%; p < 0.001) and neutral condition (81.27 ± 3.19%; p < 0.001). Reperfusion Slope was significantly lower in the cold condition (79.59 ± 3.24%) compared to neutral (80.84 ± 3.17%; p = 0.008) and hot conditions (81.54 ± 3.44%; p = 0.021). Time to peak hyperemia was significantly prolonged post-exercise across all conditions (p < 0.008). However, no significant differences were found in AUC and Δ 10 TSI (in the first 10 seconds) (p>0.005), indicating that early hyperemic responses were relatively stable regardless of temperature modulation. Discussion and conclusions. The present study examined the effects of muscle temperature on reactive hyperemia before and after high-intensity exercise. Pre-exercise, RH remained unchanged across conditions, suggesting that vascular homeostasis maintained stable endothelial function, minimizing the influence of temperature at rest. Post-exercise, temperature significantly affected Max TSI and reperfusion slope with higher values in the hot condition and lower in the cold. This suggests that exercise-induced metabolic stress increased vascular sensitivity to temperature, enhancing vascular function in heat and impairing recovery in cold. In contrast, AUC and Δ10 TSI remained stable across conditions. Time to Peak was prolonged in all conditions, indicating exercise-induced endothelial fatigue delayed RH onset. These findings indicate that temperature does influence the post exercise hyperemia, while total hyperemia and early response kinetics remain unchanged. Future research should explore chronic adaptations to temperature modulation in exercise recovery strategies. Keywords: Reactive Hyperemia, Muscle Temperature, Vascular Recovery, Near-Infrared Spectroscopy, Exercise Physiology, High-Intensity Cycling, Endothelial Function